(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In terms of developments and state-wide scaling up of services in the rural area of primary education,what will it cost financially and in terms of human resources to scale-up theseservices in all the rural areas of India what policy, institutional andgovernance reforms may be necessary so as to ensure proper service delivery? Asis well known, merely setting up more schools, for instance, is not going to beenough; higher public investments in these areas needs to be accompanied bysystemic reforms that will help overhaul the present service delivery system,including issues of control and oversight.